Language Learning with Technology Perspectives from Asia - Miller, Lindsay; Wu, Junjie Gavin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This book is about language learning with technology, offering readers theoretical insights as well as practical case studies with a focus on Asia and Asian students. Although technology is rapidly advancing and most, if not all, students are already using technology in their everyday lives, traditional teaching/learning practices still exist throughout Asia. This book provides examples, written by representative educators, from a variety of countries/regions and contexts where technology has successfully been used to enhance language learning. In addition to some everyday examples of using technology: Wikipedia, PowerPoint, Google Docs and YouTube, the book also offers the readers an insight into the future possible uses of advanced technology: Augmented Reality, Virtual Reality, Artificial Intelligence and Eye Tracking. The book presents illustrations of how teachers can, and perhaps should, be open to integrating some form of technology into in-class learning or using it to supplement out-of-class activities. .
Section 1: Introduction -- Section 2: Theories and principles of language learning with technology -- Section 3.1: Case Studies -- Case Study 1: Singapore -- Case Study 2: Thailand -- Case Study 3: Malaysia -- Case Study 4: Bangladesh -- Case Study 5: Hong Kong -- Case Study 6: Macau -- Case Study 7: Japan -- Case Study 8: Korea -- Case Study 9: Vietnam -- Section 3.2: Languages other than English -- Case Study 10: Learning Chinese in Malaysia -- Case Study 11: Learning Spanish in Japan -- Section 3.3: New theories and practices -- Case Study 12: Mainland China -- Case Study 13: Japan -- Case Study 14: Malaysia -- Section 4: The way forward.
Keywords: Language and languages$1 (BStudy and teaching.s; Education; Language Education; Education; Education